2001
DOI: 10.1096/fj.01-0445fje
|View full text |Cite
|
Sign up to set email alerts
|

A novel contractile phenotype with cardiac transgenic expression of the human P2X 4 receptor

Abstract: The P2X4 receptor is a newly identified receptor expressed in the heart cell. Its function was elucidated with cardiac transgenic (TG) expression of the receptor by using the myocardium-specific a-myosin heavy chain promoter. The presence of the transgene was determined by polymerase chain reaction by using primers specific to the receptor and the vector linker region, by Southern blotting of the genomic DNA, and by immunoblotting and immunohistochemistry of both isolated cardiac myocytes and intact hearts. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
76
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 26 publications
9
76
0
Order By: Relevance
“…Similarly, the P2 antagonist pyridoxal phosphate-6-azophenyl-2Ј,4Ј-disulfonic acid (50 M) did not block the 2-meSATP-stimulated increase in myocyte contractility (data not shown). Although more work is needed, the pharmacological features of the P2 agonist-induced contractile response of the chick embryo cardiac myocyte are similar to those of the response in adult rat and mouse cardiac myocytes (11,18). Since the P2X 4 receptor was also detected in these adult mammalian cardiac myocytes, the present data are consistent with the idea that the chick cardiac cell is a potentially good model to investigate the physiological role and biochemical property of the cardiac P2X 4 R.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, the P2 antagonist pyridoxal phosphate-6-azophenyl-2Ј,4Ј-disulfonic acid (50 M) did not block the 2-meSATP-stimulated increase in myocyte contractility (data not shown). Although more work is needed, the pharmacological features of the P2 agonist-induced contractile response of the chick embryo cardiac myocyte are similar to those of the response in adult rat and mouse cardiac myocytes (11,18). Since the P2X 4 receptor was also detected in these adult mammalian cardiac myocytes, the present data are consistent with the idea that the chick cardiac cell is a potentially good model to investigate the physiological role and biochemical property of the cardiac P2X 4 R.…”
Section: Resultssupporting
confidence: 83%
“…At later time points following the transfection with exogenous cP2X 4 R cDNA, only the 58-kDa receptor protein was present (Fig. 4b), consistent with a more complete glycosylation of the exogenous cP2X 4 R. Only the 58-kDa P2X 4 receptor was detectable in cardiac myocytes isolated from adult wild type mouse and from P2X 4 receptor transgenic mice, which showed an increased receptor-mediated contractility (11). These data suggested that the 58-kDa receptor protein, probably representing the glycosylated P2X 4 receptor, is the final and functional form of the receptor.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…cardiac failure; contraction; isoproterenol; purines; adenine nucleotide ATP HAS LONG BEEN DEMONSTRATED to stimulate cardiac myocyte contractility at submicromolar concentrations (3,4,5,18,23). Recent studies show that activation of the P2X receptor subtype of the extracellular ATP receptor family increases the contractility of both cardiac myocytes and the intact heart (3,4,5,9,17,18,23). P2X receptors are ligand-gated ion channels whose activation results in sodium and calcium entry (6,10,12,19,24).…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Interestingly, P2X4R is an important subunit of the native cardiac myocyte P2X receptor, 17 and cardiac-restricted overexpression of P2X4R can induce an enhanced contractile state of the intact heart. 20 More recently, it was found that cardiac overexpression of P2X4R increased cardiac contractility and survival in a model of myocardial infarction-induced cardiac failure. 21 It has therefore emerged as a key factor in the enhancement of cardiac performance.…”
mentioning
confidence: 99%